Práticas integrativas e complementares no SUS: revisão integrativa - Habimorad, Pedro Henrique Leonetti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
While biomedicine is indispensable to contemporary life, the growing demand for Integrative and Complementary Practices (ICP) denounces the weaknesses of this model to fully meet the diverse health needs of the population. Relying on the need for realization of the principle of comprehensiveness in SUS and meeting the WHO guidelines for deployment of traditional, complementary and alternative medicines in national health systems, the brazilian government launched in 2006 the National Policy on Integrative and Complementary Practices in the Unified Health System (UHS) (NPICP). This study aims to characterize the scientific production about the ICP in the UHS before and after the implementation of NPICP, highlighting the main weaknesses, potential and prospects indicated by the research regarding this process. We use the integrative review method, considering the time period between 2000 and 2013. Between August and November 2013, Medline databases were consulted, Lilacs, SciELO and Scopus and included 35 articles that met the following criteria: full papers published in journals relevant to the topic and written in Portuguese, Spanish and / or English. Data were analyzed using qualitative and quantitative approach, presented in tables and themes and discussed based on health comprehensiveness. It was observed that the production of ICP in UHS begins to grow in 2007, that most articles are Brazilian and are concentrated in the Lilacs database. The southeast region concentrates the largest number of articles on the subject and, among universities, the Federal University of Santa Catarina (FUSC) holds the biggest percentage of articles. Most authors hold a degree in health and doctor's degrees. Regarding the methodological approach, qualitative studies have greater representation and in relation to research design stand out from the descriptive studies. The most studied subjects were UHS users and professionals. It is observed that most of ...

Embora a biomedicina seja indispensável à vida contemporânea, a crescente procura por Práticas Integrativas e Complementares (PIC) denuncia as fragilidades deste modelo em responder integralmente às diversas demandas de saúde da população. Apoiando-se na necessidade de efetivação do principio da integralidade no SUS e atendendo as diretrizes da OMS para implantação das medicinas tradicionais, alternativas e complementares nos sistemas nacionais de saúde, o governo brasileiro lançou em 2006 a Política Nacional de Práticas Integrativas e Complementares no SUS (PNPIC). O presente trabalho se propõe a caracterizar as produções científicas acerca das PIC no SUS antes e após a implantação da PNPIC, destacando as principais fragilidades, potencialidades e perspectivas apontadas pelas pesquisas em relação a este processo. Utiliza-se o método de revisão integrativa, considerando o período temporal entre 2000 e 2013. No período entre Agosto e Novembro de 2013, foram consultadas as bases de dados da Medline, Lilacs, Scielo e Scopus e incluídos 35 artigos, que atenderam os seguintes critérios: trabalhos completos publicados em periódicos, relevantes ao tema e escritos em português, espanhol e/ou inglês. Os dados foram analisados por meio de abordagem quali-quantitativa, apresentados em tabelas e em categorias temáticas e discutidos à luz da integralidade em saúde. Observou-se que a produção sobre PIC no SUS começa a crescer em 2007, que a maioria dos artigos são brasileiros e se concentram na base de dados da Lilacs. A região sudeste concentra o maior volume de artigos sobre o tema e, dentre as universidades, a Universidade Federal de Santa Catarina (UFSC). A maioria dos autores possui graduação na área da saúde e título de doutor. Em relação à abordagem metodológica, os estudos qualitativos possuem maior representatividade e em relação ao desenho de pesquisa destacam-se os estudos descritivos. Os sujeitos...
Keywords: Sistema Único de Saúde (Brasil); Politica de saúde; Promoção da saúde; Saúde pública; Medicina integrativa; Integrative medicine